Monitoring Intervention Of Video Media Extension And Booklet To Improving Adolescent Reproductive Health Knowledge - Nanik Yuliwati; Evi Solihatul Afiah (International Journal of Health and Pharmaceutical (IJHP), 2022)
Adolescent9reproductive9health is a9healthy state involving the reproductive system, functions9and exposures during adolescence, including mental and socio-cultural health. Maintaining reproductive health during adolescence is very important, because at this time the sexual organs of adolescents are already active. Reproductive health counseling is one of the government's efforts to overcome reproductive health problems. Media that9can be used9in health education are video media and other media such as booklets. The9purpose9of this9study was9to9determine the effect of using video and booklet media on9the9level of knowledge on reproductive health in adolescents. The population were 17 students. The9sample in this9research is 120 students, 60 students counseling provided using video media and the each 60 counseling provided using are booklets. Bivariate analysis using t test. The9results of this9research9show9that the experimental group has a significant9difference between before9and after9counseling with video media (p- value 0.000 < 0.05). There9was a9significant difference9between the control group before9and9after counseling with video media (p-value 0.000 <0.05). It9can be9concluded that there is9an effect of using video media and booklets on the level of knowledge of reproductive health in adolescents. It is suggested to the masters and principals of SMK 1 Banyusari to add learning about reproductive health to students by using video and booklet media methods.